Persoalan Pengaturan Kewajiban Pemegang Paten untuk Membuat Produk atau Menggunakan Proses di Indonesia - Muh Ali Masnun; Dina Roszana (Jurnal Hukum IUS QUIA IUSTUM, 2019)
The regulation of the obligation to implement patents by patent holders to create products or use of the processes in Indonesia is still relatively problematic. For example, the Regulation of the Ministry of Law and Human Rights No. 15 of 2018 concerning the Use of Patents by Patent Holders (Permenkumham No. 15 of 2018), actually negates Article 20 of Law No.13 of 2016 concerning Patents (2016 Patent Law). This study examines and evaluates the issue of regulating the obligations of patent holders to create products or the use of processes in Indonesia. This research uses the normative juridical method by using secondary data. The results of the study concluded that the 2016 Patent Law and Permenkumham No. 15 of 2018 as a basis for its implementation is still relatively short and has several weaknesses. Such as the unclarity of when the patent starts, the scope and type of patents that must be implemented, the implementation delay is not accompanied by criteria (reasons) whether or not a delay can be made, the time limit for submitting the application for a delay that does not pay attention to the duration of patent protection, the absence of anticipatory provisions to overcome the conditions of delay request rejection from the Ministry, as well as arrangements for the extension of the delay that is not paired with a deadline and criteria for the extention allowance.